2015
DOI: 10.1007/s11999-015-4219-8
|View full text |Cite
|
Sign up to set email alerts
|

Bicruciate-retaining Total Knee Replacement Provides Satisfactory Function and Implant Survivorship at 23 Years

Abstract: Background One of the goals of a TKA is to approximate the function of a normal knee. Preserving the natural ligaments might provide a method of restoring close to normal function. Sacrifice of the ACL is common and practical during a TKA. However, this ligament is functional in more than 60% of patients undergoing a TKA and kinematic studies support the concept of bicruciateretaining (that is, ACL-preserving) TKA; however, relatively few studies have evaluated patients treated with bicruciate-retaining TKA im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…In their study, no revisions were attributable to aseptic loosening of the tibial tray. Similar findings were noted by Pritchett, who reported a 23 year survivorship of 89% in 489 BCR TKAs, with only four revisions of the femoral and tibial components [6]. In contrast, Christensen et al reported higher frequency of revision and increased radiolucent lines under the tibial tray for BCR compared to a conventional cruciate-retaining TKA [41].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In their study, no revisions were attributable to aseptic loosening of the tibial tray. Similar findings were noted by Pritchett, who reported a 23 year survivorship of 89% in 489 BCR TKAs, with only four revisions of the femoral and tibial components [6]. In contrast, Christensen et al reported higher frequency of revision and increased radiolucent lines under the tibial tray for BCR compared to a conventional cruciate-retaining TKA [41].…”
Section: Discussionsupporting
confidence: 70%
“…For example, Pritchett reported that patients preferred a BCR implant relative to a posteriorstabilized (PS) prosthesis two years post-implantation [3]. An additional study from Pritchett demonstrated a Kaplan-Meier survivorship of 89% at 23 years in a series of 489 BCR implants in 390 patients [6]. Baumann et al reported that proprioception following BCR is similar to unicompartmental knee arthroplasty and is significantly better than a PS TKA [7].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior and posterior cruciate ligament (ACL and PCL) retaining TKA, or bi‐cruciate retaining (BCR) TKA has potential advantages over contemporary TKA. Functional outcomes and implant survivorship have been reported in 22‐year long‐term follow‐up studies, with a greater number of bilateral TKA patients preferring the BCR TKA over their contralateral PS or CR TKA . In‐vitro studies have reported reduced anteroposterior laxity in BCR TKA and closer replication of native knee kinematics when compared to contemporary TKA .…”
mentioning
confidence: 99%
“…The cartilage status in other compartments can also influence the type of arthroplasty procedure selected. For patients with an intact, functional ACL, consideration may be given to bicondylar knee arthroplasty, 29 ACLretaining TKA, 30 or conventional TKA using a cruciate retaining, cruciate sacrificing, or medial pivot design.…”
Section: Discussionmentioning
confidence: 99%